ANALISIS PERHITUNGAN KETEBALAN PERISAI RADIASI PERANGKAT RIA IP10. - Benar Bukit; Kristiyanti Kristiyanti; Hari Nurcahyadi (PRIMA - Aplikasi dan Rekayasa dalam Bidang Iptek Nuklir, 2011)
CALCULATION ANALYSIS  OF THE  THICKNESS  OF RADIATION SHIELD FORTHE RIA EQUIPMENT IP10. Calculation Anal ysis has been performed on the thickness of radiation shield for the design of the Radioi mmunoassay (RIA)  IP10 counters using five detectors arranged in parall el . The calculati on is intended to ensure that the radiati on on each detector does not i nfluence each other. The radiation shield i s made of lead. The cal culation of lead thickness  was based on the principle of the l ead plates absorptive power toward  the gamma ray of a certain  energy, whi ch is the function of l inear  absorption coefficient and the material thickness. Assuming the use of Iodium-125(I-125) source with an  activity 10 µCi,  and  expecting an absorptive power of 95%, calculations showed that the required   lead thickness is equal  to  0,013 cm. Since  lead is  soft and its avail ability in the market i s limited, lead plate of 2 mm thickness are used instead, so that counti ng result for the detectors do not infl uenceeach other. ANALISIS PERHITUNGAN KETEBALAN PERISAI RADIASI PERANGKAT RIA IP10. Telah dilakukan analisis perhitungan  ketebalan perisai radiasi pada perancangan perangkat pencacah Radi oi mmunoassay (RIA) IP10 menggunakan 5 buah detektor yang disusun secara berjajar. Perhitungan dimaksudkan agar paparan radiasi yang diterima masing-masi ng detektor ti dak saling mempengaruhi. Perisai radiasi terbuat dari  pelat ti mbal (Pb). Perhi tungan  tebal  pelat timbal berdasarkan prinsip Daya Serap (DS) radiasi pelat Pb terhadap pancaran sinar   pada energi  tertentu, merupakan  fungsi dari koefi sien linier dan tebal dari bahan. Hasil  perhitungan dengan asumsi sumber radioisotop yang digunakan Iodium-125 (I-125)  dengan akti vi tas 10 µCi dan  DS yang diharapkan 95% didapatkan tebal Pb sama dengan 0,013 cm. Dengan mengingat sifat pel at Pb yang lunak dan ketersediaan ketebalan di pasaran   terbatas, maka digunakan pelat Pb tebal 2 mm, sehingga pengukuran cacahan tidak saling mempengaruhi.